Automatized project of transmissions using delphi ambient and interaction with ANSYS - Guidi, Erick Siqueira [UNESP]; De Azevedo Silva, Fernando [UNESP] (SAE International, 2008)
Projects of machines make in a conventional way involving transmission through systems of gears consumes a long time because of the large volume the graphs and tables to be consulted, as well as the difficult equations to be solved. In this work we will present a proposal whose purpose is auxiliary the designer in the dimensioning of the mechanical elements and reduce the time spends during the development of projects the spur gears. This reduce is reached through the elaboration the specialist program for automation the analytic calculations of these transmission elements, using the computer to execute the most tiresome and repetitive tasks, and therefore more susceptible the errors, in a programming language guided to objects and events, DELPHI. This specialist program also allows the construction a parametric file in function of the independents variables that make a simulation of shipments in spur gears, applying the finite elements method. This parametric file should be loaded in the simulation software, ANSYS. Copyright © 2008 SAE International.